2005
DOI: 10.1016/j.adolescence.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Young, black, and male in foster care: Relationship of negative social contextual experiences to factors relevant to mental health service delivery

Abstract: Among a small, cross-sectional sample of young Black males transitioning from foster care (n = 74), this study explored the relationship of their negative social contextual experiences to two factors relevant to the delivery of mental health services to them: cultural mistrust of mental health professionals and attitudes toward seeking professional help. Three domains of young Black male's negative social contextual experiences were measured: proximal negative experiences, distal negative experiences, and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…According to Scott and Davis (2006), when young men are depressed, they tend to distract themselves from their depression by getting engaged in enjoyable activities, thinking of other things, or ignoring their problems instead of ruminating about them. Braithwaite and Taylor (2001) suggest that African American men learn to detach themselves from their feelings.…”
Section: Depression In a Cultural Contextmentioning
confidence: 99%
“…According to Scott and Davis (2006), when young men are depressed, they tend to distract themselves from their depression by getting engaged in enjoyable activities, thinking of other things, or ignoring their problems instead of ruminating about them. Braithwaite and Taylor (2001) suggest that African American men learn to detach themselves from their feelings.…”
Section: Depression In a Cultural Contextmentioning
confidence: 99%
“…With regard to psychiatric history, certain disorders such as oppositional defiant disorder and major depressive disorder may influence the nature of the appraisals of Black males. In a previous study, Scott and Davis (2006) found that young Black males with a psychiatric history based on DSM-IV diagnostic criteria tended to have less positive attitudes toward seeking mental health services. Controlling for counseling status and history, psychiatric history, and foster care custody status, we hypothesized that more frequent negative social contextual experiences would be related to greater cultural mistrust of mental health professionals.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, analysis by Bell and Tracey identified a unitary factor structure underlying the CMI. Yet, despite the ambiguity of the factor structure, researchers have employed the full scale and combinations of the originally devised subscales in research with a variety of samples (e.g., Phelps, Taylor, & Gerard, 2001;Scott & Davis, 2006;Thompson et al, 1994).…”
mentioning
confidence: 99%